Evaluation of Fleroxacin Activity against Established Pseudomonas fluorescens Biofilms - Korber, D. R. (1994)
Scanning confocal laser microscopy (SCLM) and fluorescent molecular probes were used to evaluate the effect of the fluoroquinolone fleroxacin on the architecture of established Pseudomonas fluorescens biofilms. Control P. fluorescens biofilms were heterogeneous, consisting of cell aggregates extending from the attachment surface to maximum measured depths of ∼90 μm (mean biofilm depth at 72 h, 42 ± 28 μm) and penetrated by an array of channels. In contrast, fleroxacin-treated biofilms were less deep (mean biofilm depth at 72 h, 29 ± 8 μm), varied little in depth over large areas, and consisted of a homogeneous distribution of cells. Fleroxacin also caused cells to elongate, with cells located near the biofilm-liquid interface lengthening significantly more than cells located at the attachment surface. By using SCLM, acridine orange, and image analysis it was found that ∼59% of cells within fleroxacin-treated biofilms emitted red fluorescence whereas >99% of cells from control biofilms emitted green fluorescence. The fleroxacin-treated cells which emitted red fluorescence were observed to be the population of cells which elongated.